Haploinsufficiency of cohesin protease, Separase, promotes regeneration of hematopoietic stem cells in mice. (3rd October 2020) - Kumar, Praveen; Cheng, Haizi; Paudyal, Samridhdi; Nakamura, Lanelle V.; Zhang, Nenggang; Li, Jessica T.; Sasidharan, Rajkumar; Jeong, Mira; Pati, Debananda
Abstract: Cohesin recently emerged as a new regulator of hematopoiesis and leukemia. In addition to cohesin, whether proteins that regulate cohesin's function have any direct role in hematopoiesis and hematologic diseases has not been fully examined. Separase, encoded by the ESPL1 gene, is an important regulator of cohesin's function. Canonically, protease activity of Separase resolves sister chromatid cohesion by cleaving cohesin subunit-Rad21 at the onset of anaphase. Using a Separase haploinsufficient mouse model, we have uncovered a novel role of Separase in hematopoiesis. We report that partial disruption of Separase distinctly alters the functional characteristics of hematopoietic stem/progenitor cells (HSPCs). Although analyses of peripheral blood and bone marrow of Espl1 +/Hyp mice broadly displayed unperturbed hematopoietic parameters during normal hematopoiesis, further probing of the composition of early hematopoietic cells in Espl1 +/Hyp bone marrow revealed a mild reduction in the frequencies of the Lin − Sca1 + Kit − (LSK) or LSK CD48 + CD150 − multipotent hematopoietic progenitors population without a significant change in either long-term or short-term hematopoietic stem cells (HSCs) subsets at steady state. Surprisingly, however, we found that Separase haploinsufficiency promotes regeneration activity of HSCs in serial in vivo repopulation assays. In vitro colony formation assays also revealed an enhanced serial replating capacity of hematopoietic progenitors isolated from Espl1 +/Hyp mice. Microarray analysis of differentially expressed genes showed that Separase haploinsufficiency in HSCs (SP-KSL) leads to enrichment of gene signatures that are upregulated in HSCs compared to committed progenitors and mature cells. Taken together, our findings demonstrate a key role of Separase in promoting hematopoietic regeneration of HSCs. : Abstract : Separase haploinsufficiency in murine hematopoietic stem cells (HSCs) promote hematopoietic regeneration in vivo without altering the cellular quiescence.